2017
DOI: 10.3389/fpls.2017.00032
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Alkalinization as a Defense Response in Potato Cells

Abstract: A quantitative and robust bioassay to assess plant defense response is important for studies of disease resistance and also for the early identification of disease during pre- or non-symptomatic phases. An increase in extracellular pH is known to be an early defense response in plants. In this study, we demonstrate extracellular alkalinization as a defense response in potatoes. Using potato suspension cell cultures, we observed an alkalinization response against various pathogen- and plant-derived elicitors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…The H 2 O 2 production reaction described by Bolwell's group (Daudi et al ., ) is favoured by high pH, consistent with the pH increases reported during elicitor/PAMP responses. In potato, comparison of various PAMPs and DAMPs shows that only those causing a pH increase also elicit ‘ROS’ production (Moroz et al ., ). Is it feasible that NOX, together with the suppression of H + ‐ATPase activity could contribute to the high pH to favour type III peroxidase‐derived H 2 O 2 production.…”
Section: Production Of H2o2: Enzymes and Subcellular Locationsmentioning
confidence: 97%
“…The H 2 O 2 production reaction described by Bolwell's group (Daudi et al ., ) is favoured by high pH, consistent with the pH increases reported during elicitor/PAMP responses. In potato, comparison of various PAMPs and DAMPs shows that only those causing a pH increase also elicit ‘ROS’ production (Moroz et al ., ). Is it feasible that NOX, together with the suppression of H + ‐ATPase activity could contribute to the high pH to favour type III peroxidase‐derived H 2 O 2 production.…”
Section: Production Of H2o2: Enzymes and Subcellular Locationsmentioning
confidence: 97%
“…Proper cell size and age are important to gain a maximum alkalinization response, previously shown by Moroz et al (2017).…”
Section: Methodsmentioning
confidence: 89%
“…Using a suspension culture system, the alkalinization assay has been employed with a number of species, including grapes, poplar, Arabidopsis, tobacco, wild tomato ( S. peruvianum ), potato, sweet potato, and maize (Chang & Nick, ; Chen et al., ; Felix et al., ; Huffaker, Pearce, & Rya, ; Kunze et al., ; Moroz et al., ; Pearce & Ryan, ; Pearce et al., ; Pearce, Yamaguchi, Munske, & Ryan, ). For most studies, the method has been used to identify MAMPs, e.g., flg22 and elf18, or plant‐derived damage‐associated molecular patterns (DAMPs), e.g., systemin, RALF, AtPeps, and others.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Spongospora subterranea, and Colletotrichum coccodes) was studied using potato and Arabidopsis cells suspensions. It was shown that treatments with elicitors or zoospores from P. infestans, as well as exposure to other pathogens, induce alkalinisation of medium, ROS production and induction of defense related genes (Moroz et al, 2017). In addition, defense responses, including ROS production, defense gene expression and MAPK activation were studied in the interaction between P. capsici and Capsicum chinense cell suspensions (Nakazawa-Ueji et al, 2009).…”
mentioning
confidence: 99%